Utilization of Synthetic Steel Gases in an Additively Manufactured Reactor for Catalytic Methanation - Hauser, Alexander; Feldner, Alexander; Treiber, Peter; Grimm, Fabian; Karl, Jürgen (Sustainability, 2023)
The path to European climate neutrality by 2050 will require comprehensive changes in all areas of life. For large industries such as steelworks, this results in the need for climate-friendly technologies. However, the age structure of existing steelworks makes transitional solutions such as carbon capture, utilization and storage (CCUS) necessary as short-term measures. Hence, a purposeful option is the integration of technical syntheses such as methanation into the overall process. This work summarizes hydrogen-intensified methanation experiments with synthetic steel gases in the novel additively manufactured reactor ‘ADDmeth1’. The studies include steady-state operating points at various reactor loads. Blast furnace gas (BFG), basic oxygen furnace gas (BOFG) and three mixtures of these two gases serve as carbon sources. The methanation achieved methane yields of 93.5% for BFG and 95.0% for BOFG in the one-stage once-through setup. The results suggest a kinetic limitation in the case of BFG methanation, while an equilibrium limitation is likely for BOFG. There is a smooth transition in all respects between the two extreme cases. The reaction channel inlet temperature (Formula presented.) showed a large influence on the reactor ignition behavior. By falling below the threshold value, a blow-off occurred during experimental operation. By means of a simulation model, practical operating maps were created which characterize permissible operating ranges for (Formula presented.) as a function of the gas composition and the reactor load.
CRIS-Team Scopus Importer:2023-05-26
Keywords: BFG; BOFG; by-product gas; catalytic methanation; ignition behavior; simulation; temperature profiles